(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
the article considers an urgent problem of environmental protection - the formation of the beginning of ecological culture in children; the formation of a consciously correct attitude to objects and phenomena of nature; to develop ecological thinking; training in practical actions for nature protection